2012
DOI: 10.1111/j.1360-0443.2012.03958.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of media campaigns on smoking cessation activity: a structural vector autoregression analysis

Abstract: Tobacco control campaigns appear to be more effective at triggering quitting behaviour than pharmaceutical company NRT campaigns. Any effect of such campaigns on quitting behaviour seems to be restricted to the month of the campaign, suggesting that such campaigns need to be sustained over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 29 publications
5
42
0
Order By: Relevance
“…Our analysis shows that this dropped by two-thirds following the freeze. A recent study (which used the same source of quitline data as this study) demonstrated an effect of mass media campaigns on quitline calls in England, but not prescriptions or sales of smoking cessation medication in England and Wales [8]. It found that a 1% increase in advertising exposure led to a 0.08% increase in quitline calls in the same month; based on this estimate, the effect of the freeze on quitline calls seems bigger than expected.…”
Section: -Week Quitterssupporting
confidence: 47%
See 1 more Smart Citation
“…Our analysis shows that this dropped by two-thirds following the freeze. A recent study (which used the same source of quitline data as this study) demonstrated an effect of mass media campaigns on quitline calls in England, but not prescriptions or sales of smoking cessation medication in England and Wales [8]. It found that a 1% increase in advertising exposure led to a 0.08% increase in quitline calls in the same month; based on this estimate, the effect of the freeze on quitline calls seems bigger than expected.…”
Section: -Week Quitterssupporting
confidence: 47%
“…There is substantial international evidence that tobacco control media campaigns increase quit attempts and reduce smoking prevalence [1][2][3][4][5][6][7][8][9]; however, such campaigns are often part of multi-component tobacco control programmes, and separating the effect of mass media campaigns from other tobacco control strategies is difficult. In England, from 1999 onwards, large-scale tobacco control campaigns were run regularly as part of a comprehensive range of tobacco control policies.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are similar to a recent study of English tobacco control TV MMCs 8. Using a similar methodology, they also found that TV MMCs resulted in an immediate increase in calls to quitline, but unlike the present study there was no cumulative effect.…”
Section: Discussionsupporting
confidence: 91%
“…It includes any costs reimbursed fully or partially via prescription charges and therefore reflects most accurately the volume of prescriptions rather than simply the number of prescriptions 17. Both are regarded as important indicators of smoking cessation activity 8, 22, 23, 24.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation